Analisis Loyalitas dan Daya Beli Konsumen Terhadap Olahan Kopi Robusta di Warung Kopi My Way Jember - Syahrindra, Wendy; Lutfi’ah, Hikmatul (KUBIS, 2024)
Coffee is a drink that is popular with today's youth. It is not surprising that many coffee shop businesses have been established in Indonesia. The proliferation of coffee shops has become a source for the emergence of a creative economy using various packaged coffee preparations. One of the coffee shops that has a unique or superior product is Warung My Way, which is located in Jember Regency. The purpose of this research is to determine the factors that influence consumer loyalty and determine consumer purchasing power for Robusta Coffee at Warung Kopi My Way. The research was conducted at Warung Kopi My Way Jember using the Accidental Sampling technique with a sample size of 75 people. Research requires descriptive analysis and statistical analysis. Descriptive analysis is used to intuitively explain the data being analyzed so that it can be understood, while the statistical analysis used is binary logistics regression analysis. The results show that the factors that influence consumer loyalty are customer satisfaction, product and service quality, and barriers to switching to other brands. buying power based on public image, product and service quality, as well as barriers to moving to other countries is around 1,340; 1,058; 1.195, while based on the fairness of the trade of 0.675. This means that consumer loyalty is based on public image, product and service quality, as well as barriers to migration which influence consumer loyalty. This means that consumers will come back and carry out subsequent transactions.